AKTIVITAS ANTIBAKTERI FRAKSI n-HEKSAN, KLOROFORM, ETIL ASETAT BUNGA KAMBOJA (Plumeria alba) TERHADAP BAKTERI Staphylococcus aureus DAN Salmonella typhi - ni nyoman rupiniasih; Indriani; Syamsuddin; Abdul Rahman Razak (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2019)
Tests on the inhibition extract of n-hexane fraction, extract of chloroform fraction and extract of ethyl acetate fraction of frangipani flower (Plumeria alba) on Staphylococcus aureus and Salmonella typhi has been done. This study aims to determine the activity of frangipani flower extract on the growth of S. aureus and S. typhi bacteria. Frangipani flowers was macerated using methanol solvents. The obtained methanol extract was partitioned with n-hexane, chloroform and ethyl acetate solvents, respectively. The three extracts were tested for antibacterial activity at a concentration of 10% using the diffusion well method. The test results showed that the n-hexane, chloroform and ethyl acetate fractions showed an inhibition zone of 9.77 mm, 20.89 mm and 19.44 against S. aureus whereas S. typhi showed an inhibition zone of 15.86 mm, 27.69 mm and 21.74 mm. Keywords: Antibacterial, extract of frangipani flower, Staphylococcus aureus, Salmonella typhi.